Multiplex methylated DNA testing in plasma with high sensitivity and specificity for colorectal cancer screening. (12th August 2019) - Zhao, Guodong; Li, Hui; Yang, Zixuan; Wang, Zhenzhen; Xu, Manqiu; Xiong, Shangmin; Li, Shiming; Wu, XiaoTing; Liu, Xiaoyu; Wang, Ziwen; Zhu, Yun; Ma, Yong; et al.
Abstract: Methylated SEPT9 showed relatively low sensitivity in detecting early stage colorectal cancer (CRC) and advanced adenomas (AA) in plasma. Combination of multiple biomarkers was an effective strategy to improve sensitivity in early stage cancer diagnosis and screening. A new qPCR‐based assay combining the detection of methylated SEPT9 and SDC2 (ColoDefense test) was used. Methylation statuses of SEPT9 and SDC2 were examined in 40 sets of cancer tissues and paired adjacent tissues, 10 adenomatous polyps and 3 hyperplastic polyps (HP). Then evaluated with 384 plasma samples, including 117 CRC patients, 23 AA patients, 78 small polyps patients, and 166 normal individuals. The limit of detection of ColoDefense was about 25 pg per reaction. Both SEPT9 and SDC2 were shown by ColoDefense to be heavily methylated in CRC tissues when compared to paired paracancerous tissues and HP ( P < .01). The sensitivities for detecting AA and stage I CRC by plasma SEPT9 methylation alone were 12.1% and 65.0%, and those by plasma SDC2 methylation alone were 43.5% and 55.0%. In comparison, the sensitivities to detect AA and stage I CRC by ColoDefense improved to 47.8% and 80.0%. The overall sensitivity of ColoDefense in detecting CRC was 88.9% (95% CI: 81.4%‐93.7%) with a specificity of 92.8% (95% CI: 87.4%‐96.0%). Detection of the combinatorial biomarker of methylated SEPT9 and/or SDC2 is a powerful, convenient and highly effective strategy for early CRC screening with high sensitivity and specificity. Abstract : Colorectal cancer (CRC) is the most common malignancy of gastrointestinal tract and methylated SEPT9 showed relatively low sensitivity in detecting early stage CRC and advanced adenomas (AA) in plasma. We evaluated the performance of the new qPCR‐based assay (ColoDefense test) combining the detection of multiple methylated circulating tumor DNA biomarkers. The ColoDefense test showed high sensitivity and specificity in detecting early stage CRC (stage I) and AA in plasma when compared with methylated SEPT9 alone.